2000
DOI: 10.1136/jms.7.3.127
|View full text |Cite
|
Sign up to set email alerts
|

Maternal thyroid deficiency and pregnancy complications: implications for population screening

Abstract: Objective-To examine the relation between certain pregnancy complications and thyroid stimulating hormone (TSH) measurements in a cohort of pregnant women. Methods-TSH was measured in sera obtained from women during the second trimester as part of routine prenatal care. Information was then collected about vaginal bleeding, premature delivery, low birthweight, abruptio placentae, pregnancy induced hypertension, need for cesarean section, low Apgar scores, and fetal and neonatal death. Results-Among 9403 women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
365
3
22

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 558 publications
(410 citation statements)
references
References 15 publications
9
365
3
22
Order By: Relevance
“…Raised maternal serum TSH in the second trimester is also associated with an increased rate of fetal death after 16 weeks' gestation [37]. Other studies have found that although women treated for hypothyroidism may have higher rates of preeclampsia and caesarean section than euthyroid women, they are not at any higher risk for adverse outcomes such as fetal anomalies, fetal demise, or preterm birth.…”
Section: B-obstetrical Complications Of Maternal Hypothyroidismmentioning
confidence: 89%
See 4 more Smart Citations
“…Raised maternal serum TSH in the second trimester is also associated with an increased rate of fetal death after 16 weeks' gestation [37]. Other studies have found that although women treated for hypothyroidism may have higher rates of preeclampsia and caesarean section than euthyroid women, they are not at any higher risk for adverse outcomes such as fetal anomalies, fetal demise, or preterm birth.…”
Section: B-obstetrical Complications Of Maternal Hypothyroidismmentioning
confidence: 89%
“…In a study of women during the second trimester of pregnancy, the prevalence of fetal death was over 4-fold higher in mothers with a TSH concentration ≥6 mIU/L, compared to those whose mothers had a TSH <6 mIU/L (3.8% vs. 0.9%) [37] Untreated hypothyroidism is associated with increased risk of preeclampsia, low birth weight, placental abruption, miscarriage, and perinatal mortality [53,54]. In addition to an increased risk of low birth weight, hypothyroidism (as defined by increased serum TSH) early and late in pregnancy may also increase the rate of caesarean section [55].…”
Section: B-obstetrical Complications Of Maternal Hypothyroidismmentioning
confidence: 99%
See 3 more Smart Citations